2019
DOI: 10.3390/jcm9010099
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Horticultural Programs for Older Adults with Depressive Symptoms and Memory Problems: A Randomized Controlled Trial

Abstract: Depressive symptoms and memory problems are risk factors for dementia. Exercise can reduce these in older people, and horticultural activity can benefit people with dementia. This study assessed the efficacy of exercise and horticultural interventions for community-dwelling older adults with depressive symptoms and mild memory decline. In this randomized controlled trial, older adults (n = 89) were assigned to exercise, horticultural, or control groups. Exercise and horticultural programs included 20 weekly 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 35 publications
1
57
0
Order By: Relevance
“…According to a report in 2015, by the Ministry of Health and Welfare of Taiwan, the healthy or subhealthy accounted for 83.5% of the elderly population in Taiwan and the disabled account for 16.5% [ 2 ]. Whether healthy or disabled, as the elderly population ages they must face the decline of physiological function and cognitive function, which leads to the negative impact of their physiological, psychological, and social functions [ 3 , 4 , 5 , 6 ]. Studies have indicated that elders who contact nature or plants or engage in horticultural activities could maintain health, delay aging, and improve the benefits of physical, psychological, cognitive, and social functions [ 3 , 5 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a report in 2015, by the Ministry of Health and Welfare of Taiwan, the healthy or subhealthy accounted for 83.5% of the elderly population in Taiwan and the disabled account for 16.5% [ 2 ]. Whether healthy or disabled, as the elderly population ages they must face the decline of physiological function and cognitive function, which leads to the negative impact of their physiological, psychological, and social functions [ 3 , 4 , 5 , 6 ]. Studies have indicated that elders who contact nature or plants or engage in horticultural activities could maintain health, delay aging, and improve the benefits of physical, psychological, cognitive, and social functions [ 3 , 5 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we can use questionnaires or scales to understand more subjective mental states [ 16 , 42 ]. Commonly used questionnaires are the Profile of Mood States (POMS) [ 33 , 34 , 43 ], Life Satisfaction Index [ 5 , 16 , 44 ], stress scale [ 28 ], and depression related scale [ 6 , 15 , 18 , 24 ]. Many studies have explored how contact with nature and engagement in horticultural activities affects mental states [ 5 , 6 , 7 , 16 , 33 , 34 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The worldwide outbreak happens to provide good environments for SARS-CoV-2 mutations. The accumulation of these mutations may cause the COVID-19 to develop in an uncertain direction, which will have a huge impact on society and personal life 4 . According to other epidemiological studies, mutations in the genome of an epidemic will be inherited from the spreader to the next generation of patients.…”
Section: Introductionmentioning
confidence: 99%
“…The worldwide outbreak happens to provide good environments for SARS-CoV-2 mutations. The accumulation of these mutations may cause the COVID-19 to develop in an uncertain direction, which will have a huge impact on society and personal life 4 .…”
Section: Introductionmentioning
confidence: 99%